2019
DOI: 10.1111/hsc.12716
|View full text |Cite
|
Sign up to set email alerts
|

Link workers’ perspectives on factors enabling and preventing client engagement with social prescribing

Abstract: For a social prescribing intervention to achieve its aims, clients must first be effectively engaged. A 'link worker' facilitating linkage between clients and community resources has been identified as a vital component of social prescribing. However, the mechanisms underpinning successful linkage remain underspecified. This qualitative study is the first to explore link workers' own definitions of their role in social prescribing and the skills and qualities identified by link workers themselves as necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(119 citation statements)
references
References 17 publications
5
112
0
2
Order By: Relevance
“…While limited literature exists regarding how SP produces positive outcomes, our findings mirror themes identified in studies conducted by Hanlon et al 10 , Kellezi et al 3 and Payne et al 11 , among others that studied uptake and adherence of SP. 6,[25][26][27] Participants in Hanlon et al's study emphasized the importance of having the power to set their own priorities in regards to their health. 10 In all three studies, participants valued the personal and tailored interactions they had with their SP navigator and their use of an empathetic approach.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…While limited literature exists regarding how SP produces positive outcomes, our findings mirror themes identified in studies conducted by Hanlon et al 10 , Kellezi et al 3 and Payne et al 11 , among others that studied uptake and adherence of SP. 6,[25][26][27] Participants in Hanlon et al's study emphasized the importance of having the power to set their own priorities in regards to their health. 10 In all three studies, participants valued the personal and tailored interactions they had with their SP navigator and their use of an empathetic approach.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…This is contingent on physicians initiating these relationships; Wildman et al . () found that link workers felt that inconsistent referrals served as a barrier to performing their role. Strong state–society relationships can be used as a means to compel health professionals to prioritise relationships with LCHWs.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…However, most evidence on social prescribing to date is from the perspective of the patient and their outcomes. Various studies have shown the benefits of the link worker role to patients, and some are also starting to evaluate social prescribing from the perspective of link workers [21,22]. But the role of the GP in social prescribing is less well understood.…”
Section: Introductionmentioning
confidence: 99%